Measuring the influence of complexity on relational reasoning: the development of the Latin Square Task. - Birney DP; Halford GS; Andrews G (Educational & Psychological Measurement, 2006)
Relational complexity (RC) theory conceptualizes an individual's processing capacity and a task's complexity along a common ordinal metric. The authors describe the development of the Latin Square Task (LST) that assesses the influence of RC on reasoning. The LST minimizes the role of knowledge and storage capacity and thus refines the identification of a processing-capacity-related complexity effect in task performance. The LST is novel with one explicit rule that is easily understood by adults and children. In two studies, a test of 18 items encompassing three RC levels was administered to university (N = 73; 16-33 years) and school (N = 204; 8-19 years) students. Rasch analyses indicate that the LST scores were psychometrically stable across age groups and provides important diagnostic clues for task development. Consistent with RC theory, the LST is sensitive to parallel and serial (via segmentation) processing demands. The LST provides a strong basis for research on working memory and related constructs (fluid intelligence).